Determining the effect of vibrating wave swabbing on the functional processes in carbonate low-permeability reservoirs - Rubel, Victoriia; Rubel, Vyacheslav; Surzhko, Tetiana; Goshovskyi, Sergii (Eastern-European Journal of Enterprise Technologies, 2024)
This paper investigates the method of vibrating wave swabbing, which is used to stimulate the flow of liquid to the well. This method is known to generate mechanical waves in the soil that open microcracks and pores, increasing the flow of hydrocarbons. A carbonate reservoir with low permeability, which is quite common in the oil and gas industry, was considered as the study object. Therefore, the object of research was carbonate low-permeability reservoirs. After all, their low permeability makes the extraction of oil and gas from them a difficult task. As a result of processing, it was established that increasing the amplitude of pressure fluctuations contributes to increasing the efficiency of the vibration wave action, as the permeability of the reservoir increases more intensively, which was confirmed by the coefficient of determination, which was R2=0.92. And an increase in the frequency of oscillations, on the contrary, reduces it, because the depth of the effective zone of vibrational action decreases; in this case, the coefficient of determination was R2=0.81. To study the effect, a laboratory setup was designed that included a plunger device that generated fluid perturbations in a conditional borehole. The resulting elastic waves were measured by a manual contact vibrometer. Vibrating wave swabbing is a promising method for intensifying hydrocarbon production. The influence under investigation could be implemented in oil and gas fields with carbonate low-permeability reservoirs. This would lead to an increase in fluid production and improved efficiency of the oil and gas industry